Analysis of Balamut Performance Structure for Cultural Preservation in Southern Kalimantan - Nursugiharti, Titih; Yulianto, Agus; Bahri, Saeful; Hidayat, Roch Aris; Jahdiah, Jahdiah; Safei, Mawar (Pandawan, 2026)
Lamut is a traditional art form that has evolved and flourished alongside society. This performance art involves a solo theatrical presentation by an individual known as the Palamutan. Facing the threat of extinction due to modern societal dynamics, this study investigates lamut art, identifying the factors behind its decline, exploring methods for its revitalization, particularly among youth, and evaluating its contribution to national and local development, underscoring its cultural importance and need for preservation. This study highlight the rich cultural history of Lamut and its significance in the Banjar community. The study is to understand the decline of lamut, identify the factors affecting its practice, and propose methods to preserve it for future generations. The methodology employed is descriptive qualitative research, providing an explanatory framework for the findings. The study categorizes lamut into two types: entertainment lamut and therapeutic lamut. Results indicate that factors contributing to the decline include the long duration of performances, ritualistic aspects incompatible with Islamic teachings, and the marginalization of traditional arts in the face of modernity. The emphasis is that the preservation of lamut requires collaboration between artists, cultural practitioners, and relevant institutions to ensure its continuity.